All Days 1998
DOI: 10.2118/47369-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Elastic Wave Propagation an Isotropy and Permeability an Isotropy In an Illitic Shale.

Abstract: f T99S, %d@Y of Pel,ofaum Enginaers, Inc. This papar was prapamd for presantatmm at !he SPHISRM Eurock '98 held in Trondhelm, Nonvay, 8-10 July 1S9SThis papar was aelectad for presantatica by an SPE Program Commiftee Iolfowing revfaw of infomlafim cantalnad In an abstract submittad by the aulhorts) Contents of the papar, as -ted. haw nOl baan rwdavmd by the Swiety of Petroleum Enginaars and are Sub@cl to mrraction by the aumor{s) Tha material, as presaniad, dons not nacessmily raflact any pdaftion of the SMety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…18,19,28−32 This method is also very sensitive to fluid leakage and temperature fluctuations. 5,23 In addition, Lyu et al 33 and Sander et al 5 stated that the pulse-decay method may overestimate permeability compared to the steady-state method. Rushing et al 34 investigated the reason behind this discrepancy and concluded that this might be related to fundamental problems with the unsteady-state methodology.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19,28−32 This method is also very sensitive to fluid leakage and temperature fluctuations. 5,23 In addition, Lyu et al 33 and Sander et al 5 stated that the pulse-decay method may overestimate permeability compared to the steady-state method. Rushing et al 34 investigated the reason behind this discrepancy and concluded that this might be related to fundamental problems with the unsteady-state methodology.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the other hand, when a constant flowrate mode is applied for permeability measurement, it takes too long to arrive at equilibrium pressure. Lasswell reported that 6 to 8 weeks is required until a reasonable flow equilibrium is achieved when a light oil is used for measurement of permeability in the range of nanodarcy. Jones and Meredith, Morrow and Lockner, and El-Dieb and Hooton measured permeability of tight rocks in the range of nanodarcy in 15 to 160 h by applying only one pressure gradient across the sample. In all these studies, the core permeability is calculated based on only one flowrate value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…;Jones et al (1998);Benson et al (2010);Fazio et al (2017);Walsh (1981);Kneafsey et al (2018)). In this section, the failure caused by the progress of the hydraulic fracture occurs according toFig.…”
mentioning
confidence: 99%